2010
DOI: 10.1007/s00403-010-1090-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis type 1 (NF1) and pheochromocytoma: prevalence, clinical and cardiovascular aspects

Abstract: The aim of the study was to evaluate the prevalence of pheochromocytoma (PHEO) in patients with neurofibromatosis type 1 (NF1), and to analyze the behavior of some anthropometric and cardiovascular parameters. In 48 consecutive NF1 patients, urinary metanephrines and vanillylmandelic acid excretion were assessed. The body mass index (BMI), waist circumference (WC), ambulatory blood pressure monitoring (ABPM), echocardiography and ultrasound carotid arterial wall evaluation were performed. In NF1 patients, 11 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 37 publications
4
87
0
5
Order By: Relevance
“…A summary of a thorough review (Walther et al 1999a) together with more recent studies (Amar et al 2005, Bausch et al 2007, Mannelli et al 2009, Zinnamosca et al 2011, including a total of 216 NF1 patients with PCC or PGL, showed that 95% of the patients had PCC and 6% had PGL, all of which were sympathetic. Fourteen percent of the patients displayed bilateral PCC, 9% developed malignant disease, and the mean age at presentation was 42 years.…”
Section: Nf1 Syndromementioning
confidence: 99%
“…A summary of a thorough review (Walther et al 1999a) together with more recent studies (Amar et al 2005, Bausch et al 2007, Mannelli et al 2009, Zinnamosca et al 2011, including a total of 216 NF1 patients with PCC or PGL, showed that 95% of the patients had PCC and 6% had PGL, all of which were sympathetic. Fourteen percent of the patients displayed bilateral PCC, 9% developed malignant disease, and the mean age at presentation was 42 years.…”
Section: Nf1 Syndromementioning
confidence: 99%
“…It is crucial to identify these tumors for several reasons (7). First, PHEOs are classically recurrent in genetic syndrome, including NF1, with a proportion between 10 and 20% (9,12,14). Therefore, adrenocortical sparing surgery represents a major concern and has gained popularity in the last few years in various indications (38,39,40).…”
Section: :4mentioning
confidence: 99%
“…As it is a rare tumor, screening is not recommended in asymptomatic patients (7,8). However, Zinnamosca et al (9) in 2011 found a PHEO prevalence of 14% in a population of 48 consecutive NF1 patients, suggesting an underestimation of the prevalence of these lesions in this population. The objective of the study was to evaluate the prevalence and the interest of a systematic screening of PHEO in a NF1 population.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Zinnamosca et al (21) of 48 patients with NF-1-related PHEO (NF1-PHEO) and an average age of 39 years, ~85% of patients had single adrenal tumors, whilst 15% had bilateral adrenal tumors. In addition, 57% of patients exhibited the clinical features of high catecholamine concentration, including headache, heart palpitations, sweating and hypertension.…”
Section: Discussionmentioning
confidence: 99%